To rewrite the expression \(27 \frac{1}{2} \times 27 \frac{1}{4}\), we first convert the mixed numbers into improper fractions.
-
Convert \(27 \frac{1}{2}\): \[ 27 \frac{1}{2} = 27 + \frac{1}{2} = \frac{54}{2} + \frac{1}{2} = \frac{55}{2} \]
-
Convert \(27 \frac{1}{4}\): \[ 27 \frac{1}{4} = 27 + \frac{1}{4} = \frac{108}{4} + \frac{1}{4} = \frac{109}{4} \]
Now, we can rewrite the original expression using the improper fractions:
\[ 27 \frac{1}{2} \times 27 \frac{1}{4} = \frac{55}{2} \times \frac{109}{4} \]
Thus, the rewritten expression is:
\[ \frac{55}{2} \times \frac{109}{4} \]